Negotiating faith in a hospital bed: A qualitative exploration of barriers to prayer (Solah) among hospitalised Muslim orthopaedic patients in Malaysia - Mohd Ariff Sharifudin; Yuzana Mohd Yusop; Mai Nurul Ashikin Taib; Mohd Fitri Omar; Al Hafiz Ibrahim; Anas Mohd Yunus (Belitung Nursing Journal, 2026)
Background: For Muslim patients, performing the five daily prayers (Solah) is a non-negotiable pillar of faith and a vital source of spiritual solace during illness. In Malaysia, the Ibadah-Friendly Hospital (IFH) framework was established to support this need within holistic care. However, adherence remains low, particularly among patients with physical limitations, such as orthopaedic conditions, suggesting a significant gap between policy and lived experience. Objective: This study aimed to explore in-depth the lived experiences, perceptions, and multifaceted barriers faced by hospitalised Muslim orthopaedic patients in fulfilling their obligatory prayers. Methods: A qualitative descriptive case study design was employed. Purposive sampling was used to recruit 16 Muslim patients from the orthopaedic wards of a tertiary hospital on the East Coast of Malaysia. Data were gathered via semi-structured, in-depth interviews and non-participant observations between July 2023 and February 2024. Thematic analysis was conducted using the Framework Method, facilitated by the Atlas.ti software. Trustworthiness was ensured through researcher reflexivity, audit trails, and team debriefing. Results: Three primary themes emerged from the data: (1) Negotiating Obligation and Leniency, where patients held a common misconception that religious concessions (rukhsah) permitted complete postponement rather than adaptation of prayer; (2) The Embodied Struggle of Purity and Piety, capturing profound distress over ritual impurity from medical devices (catheters, diapers) and practical hurdles with inadequate ablution facilities and missing prayer attire; and (3) The Silent Gap in Supportive Care, highlighting a systemic failure where patients perceived nurses as too busy for spiritual support, experienced gender-related discomfort, and found existing IFH facilities (e.g., prayer kits) inaccessible or unknown. Conclusion: The barriers are complex, intertwining knowledge gaps, embodied distress, and systemic shortcomings. Moving beyond infrastructural provisions, a patient-centred approach is urgently needed. This includes proactive nursing assessment of spiritual needs, tailored patient education on rukhsah, gender-sensitive assistance protocols, and training that empowers nurses to provide holistic, culturally competent care that truly supports patients’ spiritual well-being.